Morphological assessment of tissue repair in complex with perftoran chronic relapsing crack lips in the experiment (Эндодонтия Today)
The results of morphologic characteristics of healing lips' tissues in dynamics of experimental modulating of chronic relapsing lips' clefts (CRLC) were discussed in this work; the estimation of efficacy complex therapy was given. Morphologically was proved that complex treating with using Perftoran that promotes real acceleration in process of healing lips' tissues in comparison with traditional treating. Such effect of therapy is explained by local protective influence of Perftoran and as well as bactericide and bacteriostatic properties.